2020
DOI: 10.29129/inujgse.543701
|View full text |Cite
|
Sign up to set email alerts
|

Akılcı Duygusal Davranışçı Yaklaşımına Dayalı Özgüven Geliştirme Programının 7. Sınıf Öğrencilerinin Özgüven Düzeylerine Etkisi

Abstract: The aim of the present study was to investigate the effect of "Selfconfidence Development Program Based on Rational Emotional Behavioral Therapy Approach" on self-confidence levels of seventh grade students. In the direction of purpose of study; it was examined whether the self-confidence points of the participants in the experimental and control groups changed significantly. Design & Methodology: An experimental design, with a treatment and notreatment control group and two measurements (pretest and posttest)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…In Sert's (2022) study "The Effect of Sports on Self-Confidence Levels of University Students", it was found that there was a statistically significant difference between the self-confidence levels of students depending on gender and sports activities. On the other hand, it was determined that the age variable did not show any evidence of a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…In Sert's (2022) study "The Effect of Sports on Self-Confidence Levels of University Students", it was found that there was a statistically significant difference between the self-confidence levels of students depending on gender and sports activities. On the other hand, it was determined that the age variable did not show any evidence of a significant difference.…”
Section: Discussionmentioning
confidence: 99%